The impact of sports and recreational hiking with bicycles on the state of the cardiorespiratory system of Chinese students - Ban Zhijing; Tatiana Skaliy; Andrzej Ostrowski; Nurlan Minzhanov; Madina Alpysbayeva; Maryna Prudnikova (Слобожанський науково-спортивний вісник)
Background and Study Aim. In the modern educational space, active forms of recreational and health activities are becoming increasingly important, promoting physical development, health promotion and the formation of a healthy lifestyle among student youth. Cycling tourism is one of the types of active tourism based on travel using a bicycle as the main means of transportation. It combines recreational, educational and sports aspects, promoting the harmonious development of the individual. This type of tourism has a number of specific features that determine its popularity, in particular among student youth. The purpose of the study is to identify the impact of sports and recreational hiking with bicycles on the state of the cardiorespiratory system of Chinese students.